Efficacy of micronutrients powder supplementation on growth and iron status of Orang Asli children in Selangor, Malaysia - Shaari, Nur Dayana (2022)
In Malaysia, the prevalence of undernutrition and anaemia in Orang Asli (OA) children under five are relatively higher than the general population, even though many strategies have been implemented. The effect of micronutrients powder (MNP) has been indicated as a recuperative, but not a preventive strategy of child undernutrition. MNP was developed and formulated by World Health Organisation (WHO) and produced by DSM Nutritional Products in Selangor. To date, MNP is not commercially available in market. This study aimed to determine the effect of MNP (containing 15 micronutrients) on growth, iron status and dietary intakes as a prevention of underweight, stunting, wasting and anaemia among OA children with normal nutritional status (normal in weight-forage/ WAZ, length-for-age/ LAZ, weight-for-length/ WLZ and haemoglobin level) at baseline. In phase one, a feasibility study was conducted among 25 OA children aged 6- 31 months in Negeri Sembilan to determine the MNP compliance, acceptance, preference, and adverse effect. The children received three MNP sachets weekly for 5 weeks. In phase two, a cluster randomised controlled trial was conducted with 98 children aged 6-24 months from OA villages in Selangor. The children were assigned randomly into two groups: 49 children in intervention group received three MNP sachets weekly for 12 months plus health and nutrition advice, while 49 children in control group received health and nutrition advice. Growth (weight, length, WAZ, LAZ, WLZ) and iron status (haemoglobin) were the primary outcomes, while dietary intake (energy, nutrients, food group) was the secondary outcomes. Analysis for the feasibility study was based on descriptive statistics, whereas ANCOVA using General Linear Model (GLM) for repeated measures was performed in the trial (per protocol analysis). The findings of the feasibility study showed a high compliance, no adverse effect and no changes in foods mixed with MNP. During the trial, 43 and 44 children remained in intervention and control group, respectively. For the trial, the results were presented in 3 models. Model A controlled for age and gender, Model B controlled for age, gender and proportion of children meeting iron recommendation at baseline, and Model C controlled for age, gender, proportion of children meeting iron recommendation and % energy from protein at baseline. The results revealed length and LAZ were significantly different between groups (in Model A and B, but none in Model C). Other indicators such as weight, WAZ, WLZ, haemoglobin and dietary intakes were not significantly different. The rate of stunting in control group was significantly five times higher than intervention group at month 12. In conclusion, the feasibility study revealed that MNP was feasible for a randomised controlled trial among OA children in Selangor. The randomised controlled trial in Selangor confirmed that MNP given three times weekly for 12 months and provided with health and nutrition advice can improve length, LAZ and prevent stunting among OA children but no impact on weight and haemoglobin. However, future studies with diverse sub-tribes of OA would provide more information on the effect of MNP on growth, iron status and dietary intake of children.